How Green are European Curricula? A Comparative Analysis of Primary School Syllabi in Five European Countries. (December 2014) - Hanisch, Anna; Rank, Astrid; Seeber, Günther
The authors conducted a cross-national curriculum analysis as part of a European Union Comenius project regarding the implementation of an online tool to foster environmental education (EE) in primary schools. The overall goal was to determine the extent and intensity that EE is embedded in the syllabi of five European countries. To this end, the authors developed a categorical analysis framework and undertook a content analysis. In addition to the general goals and contents of EE, they researched in particular the inclusion of the topics 'waste', 'water' and 'energy' in primary school curricula. The results highlight differences and commonalities with regard to goals, contents and methodological requirements, and they confirm the relevance of EE in European school curricula.